Relationships between crystal structure and microwave dielectric properties of Li2(Mg1−xCox)3TiO6 (0 ≤ x ≤ 0.4) ceramics. Issue 17 (1st December 2017) - Pan, H.L.; Cheng, L.; Wu, H.T.
Abstract: Li2 (Mg1−x Cox )3 TiO6 (x = 0, 0.1, 0.2, 0.3, 0.4) ceramics were prepared using the conventional solid-state reaction method. Effects of Co-substitution on the crystal structure, sintering characteristics, micro–structures, microwave dielectric properties and Raman spectra were investigated. Co-substitution would affect the crystal structure and further influence the microwave dielectric properties. On the basis of the chemical bond theory and Rietveld refinement, some intrinsic factors such as the lattice energy, bond ionicity were calculated to explain the variations of the microwave dielectric properties. Ti–O and Li–O bonds played major role in influencing intrinsic factors and correlations between intrinsic factors of Ti–O, and Li–O bonds and microwave dielectric properties were established. With the increase of x values, the dielectric constant ( ε r ) gradually increased, which could be explained by the variations of the polarizability, bond ionicity of Ti–O bonds, and Raman vibration modes. The decrease of the quality factor ( Q·f ) could be predicted by the decrease of the bond valence, packing fraction and lattice energy of Ti–O bonds. The temperature coefficient of resonant frequency ( τ ƒ ) significantly correlated with the bond energy of Li–O bonds and thermal expansion coefficient of Ti–O bonds.